1980
DOI: 10.1073/pnas.77.1.629
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic membrane potential affects transmitter release in an identified neuron in Aplysia by modulating the Ca 2+ and K + currents

Abstract: We have examined the relationships between the modulation of transmitter release and of specific ionic currents by membrane potential in the cholinergic interneuron LIO of the abdominal ganglion of Aplysia californica. The presynaptic cell body was voltage-clamped under various pharmacological conditions and transmitter release from the terminals was assayed simultaneously by recording the synaptic potentials in the stsynaptic cell. When cell L1O was voltageclamped from a holding potential of -60 mV in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
1
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 35 publications
5
56
1
1
Order By: Relevance
“…Subthreshold depolarization can lead to Ca 2ϩ influx and an enhancement of neurotransmitter release (Shapiro et al 1980;Turecek and Trussell 2001). However, our data, and those of Katz and Frost (1995b) suggest that this is not the mechanism by which DSI enhances C2 distal neurite spike-evoked Ca 2ϩ signals or transmitter release.…”
Section: Possible Mechanisms By Which Dsi Enhances C2 Spike-evoked Cacontrasting
confidence: 52%
“…Subthreshold depolarization can lead to Ca 2ϩ influx and an enhancement of neurotransmitter release (Shapiro et al 1980;Turecek and Trussell 2001). However, our data, and those of Katz and Frost (1995b) suggest that this is not the mechanism by which DSI enhances C2 distal neurite spike-evoked Ca 2ϩ signals or transmitter release.…”
Section: Possible Mechanisms By Which Dsi Enhances C2 Spike-evoked Cacontrasting
confidence: 52%
“…4 A and B), a treatment that blocks Ca2+-activated K+ current (18,23,27). IKCa, although at holding potential -40 mV a part of the resting leakage conductance is a Ca24-activated K+ current (13). (C) The slow time constants of decay of PTP (e) and post-tetanic Ca2"-activated K+ (0) currents are plotted as afunction of time after EGTA injection.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these analyses have been compromised because tetanic stimulation also gives rise to membrane potential changes in the presynaptic terminals that may have secondary effects on release, masking the actual time course of the facilitated release process. Recently, neurons have been described in Aplysia in which presynaptic release sites are accessible to intracellular electrodes and can be studied under voltage-clamp conditions, in which secondary changes in membrane potential can be controlled (13)(14)(15). One of these neurons, the identified cholinergic cell L10, makes connections to follower cells that undergo PTP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A totally different scenario has been observed in the Aplysia (475,486,487) and the leech (382). In these studies on connected pairs of neurons, the authors reported that constant or transient depolarization of the membrane potential in the soma of the presynaptic neuron facilitates synaptic transmission evoked by single action potentials, in a graded manner (Fig.…”
Section: Changes In Presynaptic Voltage Affect Synaptic Efficacymentioning
confidence: 98%